From here to eternity - Zinnemann, Fred 1907-.; Adler, Buddy 1906-1960.; Taradash, Daniel 1913-.; Jones, James 1921-1977.; Columbia Pictures (Firm). (Calif. Columbia Pictures, 1963)
In 1941, at a peacetime army camp in Hawaii, a captain's wife and a career soldier fall in love, while a private is cruelly punished for refusing to box on his unit's team.
Disc 1: 60 min. -- disc 2: 59 min.
Based upon the novel by James Jones.
VCD.
Academy Award for Best Picture, Best Actor in a Supporting Role, Best Actress in a Supporting Role, Best Director, Best Writing (Screenplay), 1953 ; Cannes Film Fetival Special Award, 1954 ; Golden Globes Best Motion Picture Director, Best Supporting Actor, 1954.
Burt Lancaster, Montgomery Clift, Deborah Kerr, Donna Reed, Frank Sinatra.
Keywords: War films; World War, 1939-1945 -- Drama; Feature films